The Importance of Virtual Reality in the Conservation of Cultural Heritage: An Examination of the Penataran Temple Case Study in Blitar Regency, East Java - Subchan, Nur (Knowledge Garden: International Journal of Library Studies, 2024)
Introduction: Visualization of digital archives and applications play a crucial role in preserving cultural heritage. Utilizing efficient 3D scanning, modeling, and deep learning-based reconstruction techniques enables the revelation of hidden parts of Penataran Temple Sample in Blitar Regency, East Java. This research emphasizes the utilization of virtual reality (VR) systems as digital repositories for Penataran Temple Example, facilitating in-depth exploration of this cultural asset. The importance of applications such as guided tours, computer-aided design, and geographic information systems increases in the examination of cultural heritage, offering a deeper and more comprehensive understanding of the preserved cultural wealth.Methods: The methodology used in this research includes photogrammetry, accurate photogrammetric assessment, and the utilization of deep learning. Information obtained from these three avenues is combined to construct a three-dimensional Point cloud, serving as the foundation for the digital repository of Penataran Temple Sample. Virtual reality (VR) platforms enable individuals to observe the temple through both first-person and aerial perspectives, featuring customizable interfaces within the virtual reality setting.Results: The research activities are dedicated to creating a digital repository for Penataran Temple Sample located in Blitar Regency, East Java using 3D Point cloud data. Data acquisition of Point cloud for comprehensive coverage of temple structures and hidden reliefs is achieved through the application of advanced photogrammetric measurements and deep learning technology. A virtual reality (VR) system is developed to offer deep visualization capabilities, including first-person perspectives and aerial views, fostering a profound understanding of the cultural significance and architectural design of the temple. To enhance the realism of the VR experience and enable mapping functions, a 3D simulation engine is incorporated. The utilization of the first-person perspective allows detailed virtual exploration and collision detection, while aerial views contribute to a comprehensive understanding of the temple architecture.Discussion: The digital archive system of Penataran Temple Sample leverages Virtual Reality (VR) technology to integrate 3D Point cloud data from various sources. This system facilitates both first-person perspectives and aerial perspectives, allowing comprehensive examination and in-depth understanding of the temple architectural layout. Accurate 3D data generation is achieved through the utilization of Unmanned Aerial Vehicles (UAVs), photogrammetry technology, and deep learning techniques.Conclusion: The investigation focuses on the utilization of VR technology as a digital repository at Penataran Temple Sample, employing 3D Point cloud methodology. Its primary aim is to provide engaging visual encounters and comprehensive understanding of the architectural complex. Furthermore, this research will encompass detailed 3D measurements and the creation of high-precision VR renderings of the complete temple structures. Additionally, there are opportunities to design VR applications for remote utilization and to produce stereoscopic perspectives through holographic means. The anticipation is that VR will play a significant role in the preservation and interpretation of the heritage of Penataran Temple Sampled in Blitar Regency, East Java, while also demonstrating potential for diverse applications across various platforms and settings.